Editorial Foreword - Editorial Team (IKAT: The Indonesian Journal of Southeast Asian Studies, 2017)
Undeniably a region in change, interest in Southeast Asia is growing. With this growth comes an increase in academic works written about the region, adding to an already impressive canon. With this background in mind, the Center for Southeast Asian Social Studies (CESASS) at the Universitas Gadjah Mada, Yogyakarta, Indonesia is proud to publish IKAT: The Indonesian Journal of Southeast Asian Studies. This journal welcomes and facilitates exchange in academics and disseminates knowledge produced through this growing interest in Southeast Asia.The name IKAT was adopted to reflect a shared practice found in Southeast Asia. It is derived from the word Tenun Ikat, meaning woven fabric, which is a common textile in the region. In addition, IKAT is an Indonesian word, which means to bind, bundle, tie, or bunch. It is our hope that the publication of the IKAT Journal will serve as a platform for those interested in Southeast Asia, binding together those with a common geographical interest. As a means to unite the region, IKAT is open to contributions from all disciplines. This interdisciplinarity enables us to examine and reflect upon Southeast Asia from a plethora of perspectives, each focusing on diverse issues.